Comprehensive Review on the Multifaceted Properties of Ocimum sanctum (Tulsi): Antimicrobial, Antioxidant, Anti-inflammatory, Antidiabetic and Ecological Benefits with Cultivation Insights - Verma, Sunita; Singh, Shailja (Indian Forester, 2025)
Ocimum sanctum (Tulsi), revered for its medicinal, ecological, and agricultural significance, has garnered scientific interest for its diverse benefits. This review highlights Tulsi’s therapeutic potential, including antimicrobial, antioxidant, anti-inflammatory, antidiabetic, and adaptogenic properties. Its effectiveness against pathogens and chronic conditions underscores its role as a natural remedy. Additionally, Tulsi supports mental health through its adaptogenic effects and plays a vital ecological role in pest and fungal control. Its adaptability to diverse climates enhances its agricultural viability. Standardizing Tulsi extracts ensures therapeutic efficacy and safety, affirming its relevance in traditional and modern applications.